2020
DOI: 10.1002/anie.202006218
|View full text |Cite
|
Sign up to set email alerts
|

N6‐Isopentenyladenosine in RNA Determines the Cleavage Site of Endonuclease Deoxyribozymes

Abstract: RNA-cleaving deoxyribozymes can serve as selective sensors and catalysts to examine the modification state of RNA. However,s ite-specific endonuclease deoxyribozymes that selectively cleave post-transcriptionally modified RNAare extremely rare and their specificity over unmodified RNAi s low.W ereport that the native tRNAmodification N 6-isopentenyladenosine (i 6 A) strongly enhances the specificity and has the power to reconfigure the active site of an RNA-cleaving deoxyribozyme.Using in vitro selection, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Production of CKs through tRNA degradation is localized mainly in the cytosol. Generally, tRNA modifications contribute to an increased adaptation to environmental conditions through the control of translational efficiency and fidelity, in addition to reading frame maintenance ( Dabravolski, 2020 ; Liaqat et al, 2020 ). Following the degradation of the modified tRNA molecules, c Z-type CKs are produced.…”
Section: Introductionmentioning
confidence: 99%
“…Production of CKs through tRNA degradation is localized mainly in the cytosol. Generally, tRNA modifications contribute to an increased adaptation to environmental conditions through the control of translational efficiency and fidelity, in addition to reading frame maintenance ( Dabravolski, 2020 ; Liaqat et al, 2020 ). Following the degradation of the modified tRNA molecules, c Z-type CKs are produced.…”
Section: Introductionmentioning
confidence: 99%
“… [4a] The bulkier and more hydrophobic N 6 ‐isopentenyladenosine (i 6 A) in the RNA had a much stronger activating effect on deoxyribozyme‐catalyzed RNA cleavage, leading up to 2500‐fold faster cleavage of the i 6 A‐modified versus unmodified RNA substrate. [4b] …”
mentioning
confidence: 99%
“…We found that DNA enzymes activated by m 6 A reached 5–10‐fold faster cleavage rates for modified vs. unmodified substrate [4a] . The bulkier and more hydrophobic N 6 ‐isopentenyladenosine (i 6 A) in the RNA had a much stronger activating effect on deoxyribozyme‐catalyzed RNA cleavage, leading up to 2500‐fold faster cleavage of the i 6 A‐modified versus unmodified RNA substrate [4b] …”
Section: Figurementioning
confidence: 94%